Direct reprogramming of mouse fibroblasts into neural cells via Porphyra yezoensis polysaccharide based high efficient gene co-delivery - Yu, Qingtong (J Nanobiotechnology, 2017)
BACKGROUND: The cell source for transplantation therapy is always a prerequisite question to be solved in clinical applications. Neural cells are considered non-regenerable, which highly restrict their application in the treatment for nerve injury. Therefore, neural trans-differentiation based on gene transfection provides a new solution to this issue. Compared to viral strategy, non-viral gene delivery systems are considered as a more promising way to achieve this aim. This study centers on a novel application of Porphyra yezoensis polysaccharide as a non-viral gene carrier for the neural trans-differentiation of mouse fibroblasts. RESULTS: Ethanediamine modified P. yezoensis polysaccharide (Ed-PYP) served as a gene carrier and a group of plasmids that encode Ascl1, Brn4, and Tcf3 (pABT) self-assembled into nanoparticles. Results demonstrated that Ed-PYP–pABT nanoparticles at Ed-PYP: pABT weight ratio of 40:1 was the optimal candidate for gene delivery. ELISA assay revealed the highest expression levels of NGF, BDNF and SHH at 14 days after last transfection. Immunofluorescence and western blot assays also showed robust expression of neural markers including Nestin, GFAP, β-3tubulin, NF200, GAP43 and MAP2, in induced 3T6 cells at this time point. CONCLUSION: Overall, these findings indicated that the P. yezoensis polysaccharide-based non-viral gene co-delivery system is a promising strategy for the generation of neural cells, which might facilitate the developments in the recovery of neural injuries. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12951-017-0317-y) contains supplementary material, which is available to authorized users.